EFEKTIVITAS BAHAN AJAR PROBLEM SOLVING BERBASIS OPEN- ENDED DALAM PEMBELAJARAN MATEMATIKA UNTUK MENGEMBANGKAN KEMAMPUAN PENALARAN MAHASISWA PGSD - Jasmaniah, Fachrurazi, dan Ety Mukhlesi (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2017)
This study focuses to see the effectiveness of the use of teaching materials based on open-ended problem solving, a research that had resulted from the previous year as acontinuation of the study of research and development (R & D). The preliminary studiesand the development of teaching materials were carried out in the first year. In thesecond year it would be the evaluation phase to see the effectiveness of the trial use ofteaching materials. To view this effectiveness the researcher would evaluate the increasein reasoning abilities of the students, activity of lecture, activity of students in thelearning and teaching materials, students response to problem solving based on openendedquestion. The samples in this study were taken from two units of lectures onStudy Program Primary School Teacher (PGSD) Almuslim University. Each unit wouldbe subject to different actions, where the unit got learning with teaching materials basedon open-ended problem solving and other units without the use of the teachingmaterials. Based on the result of the study, some conclusions were found, including; (1)there is a difference between the increase in reasoning abilities of students studyingteaching materials based on the open-ended problem solving with students wo studiedwithout using the teaching materials; (2) In general, the activity of students and lecturers were observed in the study by using teaching materials based on the open-ended problem solving in both categories; (3) Based on questionnaire student responsetowards learning mathematics by using teaching materials based open ended problemsolving is very positive. Thus it can be stated that the teaching materials based on theopen-ended problem solving were very effective to be applied to the study ofmathematics at the Almuslim University PGSD Department to increase studentsreasoning skills.Keywords: Problem Solving Teaching Material Based Open-Ended, Attitude Students,Lecturers and Students Activities, and Mathematical Reasoning AbilityÂ